Application of the visual analytics in support of military decision making - Бойченко, А. В. (Інститут проблем реєстрації інформації НАН України, 2024)
Visualization is widely used to support tasks in the process of decision support and predictive analytics. The main usage covers data cleaning, research analysis and diagnostics. Military maps are the most important tools for analyzing the situation and supporting decision-making at all levels. Incorporating geospatial and temporal data is critical for sophisticated data visualization and analysis in military information systems. Іintegration of geospatial data (latitude, longitude and altitude), as well as temporal data covering time and duration of operations, improves situational awareness. This study examines features of information visualization technologies and visual analytics for decision-making in the military sphere. It has been carried out an expert assessment procedure for tools compliance into given requirements and establish pairwise comparisons matrices. Using of visualization and visual analytics tools allows increase management military decisions effectiveness accelerating analysis of large dimensions of information and simultaneous indicators and scenarios review. The work has demonstrated the key requirements to implementation of information’s visualization and visual analytics tools in military management decision support systems. Issues of using information visualization and visual analytics tools are active area for exploration in Institute for Information Recording of the National Academy of Sciences of Ukraine Modeling complex. The results will become a segment of Managing forces and means Armed Forces automated system, that will integrate management elements of strategic, operational and tactical levels into a single information-functional capacity. Choice of specific means and methods, in particular, geospatial data standards and modeling tools, will be based on how well they satisfy the established requirements. Tabl.: 5. Fig.: 4. Refs: 15 titles.